Solid-State Fermentation of Wheat Bran with Clostridium butyricum: Impact on Microstructure, Nutrient Release, Antioxidant Capacity, and Alleviation of Ulcerative Colitis in Mice - Heng Zhang; Min Zhang; Xin Zheng; Xiaofang Xu; Jiawen Zheng; Yuanliang Hu; Yuxia Mei; Yangyang Liu; Yunxiang Liang (MDPI AG, 2024)
This study investigated the effects of solid-state fermentation with Clostridium butyricum on the microstructure of wheat bran, the release of dietary fiber and phenolic compounds, and antioxidant capacity. Compared with unfermented wheat bran, insoluble dietary fiber and phytic acid content decreased, whereas soluble dietary fiber and water-extractable arabinoxylan content increased in C. butyricum culture. Because of the increased release of phenolic compounds, such as ferulic acid and apigenin, and organic acids, such as isobutyric acid, the antioxidant capacity of the culture was considerably improved. Furthermore, the culture of C. butyricum treated with dextran sulfate sodium-induced ulcerative colitis in mice enhanced the expression of intestinal mucus and tight-junction proteins, modulating the gut microbiota structure, increasing the levels of short-chain fatty acids in the intestine, and restoring the essential functions of the gut microbiota. These anti-inflammatory effects stemmed from the combined action of various effective components.